No-till farming activites in some Umanapu (agroforestry land) on earthworm diversity: a case study in Detusoko District, Ende Regency - Agustinus J.P Ana Saga; Kristono Yohanes Fowo (Jurnal Penelitian Kehutanan Wallacea, 2022)
No-till farming (NTF) is an agricultural activity without tillage process, so it can minimize damage to soil structure, reduce erosion, and reduce the decrease in soil organic matter content related to the presence of earthworms. The purpose of this study was to determine the activity of no-till farming on earthworm diversity. Exploration of earthworms was carried out by hand sorting and monolith sampling methods in Umanapu (agroforestry) of Clove, Cocoa, Candlenut, Coffee and intensive tillage farms. The earthworms were identified by observing the morphology characteristics. In addition, the observation of biomass and population of earthworms, and environmental factors were also carried out. The results showed that there were four genera of endogeic and epigeic worms, namely Lumbricus, aMegascolex, Perithima and Pontoscolex. Diversity index (H'), maximum diversity (H'max) and species evenness (E) of earthworms in intensive tillage agriculture were low but in Umanapu of Clove, Cocoa, Candlenut and Coffee were moderate. The earthworm populations, earthworm biomass (g m2) and the ratio of biomass and population of earthworms (B/P) in Umanapu of Clove, Cocoa, Candlenut and Coffee were equal and significantly different from intensive tillage. The importance value index (IVI) in Umanapu of Clove, Cocoa, Candlenut, Coffee and intensive tillage agriculture were dominated by the Pontoscolex genus. In addition, the environmental conditions such as temperature and pH of soil at each location in Umanapu were not different, as well as the environmental temperature and humidity. NTF can maintain and sustain the existence of species, population and IVI of earthworms, so that soil biological properties are still maintained.